The Audiovisual-Based Health Education as a Therapeutic Modality for Managing Anxiety in CKD Patients Facing Fluid Intake Limitations - Firmanda, Giovanni Iga; Wahyuningsih, Aries (Adi Husada Nursing Journal, 2025)
Chronic Kidney Disease (CKD) patients undergoing hemodialysis often experience heightened levels of anxiety due to complex treatment regimens and strict fluid intake restrictions. This study aimed to evaluate the effectiveness of an audiovisual intervention in reducing anxiety levels among CKD patients. A pre-experimental one-group pretest-posttest design was employed, involving 60 CKD patients selected through purposive sampling. The intervention consisted of a five-minute audiovisual presentation combining fluid restriction education and relaxation techniques. The independent variable was the audiovisual intervention, while the dependent variable was the patients' anxiety levels. Anxiety was assessed using the standardized Generalized Anxiety Disorder-7 (GAD-7) questionnaire, administered both before and after the intervention. Data analysis was conducted using paired t-tests to compare mean anxiety scores, with a significance threshold set at p < 0,05. Prior to the intervention, the majority of participants (56.6%) experienced moderate anxiety, while 41,6% had mild anxiety, and 1.8% had severe anxiety. After the intervention, a notable shift occurred: 91,6% of patients reported mild anxiety, and only 8,4% experienced moderate anxiety, with no cases of severe anxiety. The average anxiety score significantly decreased from 11,03 to 7,57, resulting in a mean difference of 2,466 and a p-value of 0,000, indicating a statistically significant improvement. These findings suggest that audiovisual media are effective in reducing anxiety in hemodialysis patients by improving their understanding of fluid management and promoting relaxation. The engaging and accessible nature of the intervention empowered patients and helped alleviate emotional distress, supporting its use in clinical settings as a complementary therapeutic tool.